#TITLE_ALTERNATIVE# - M. (NIM 23806003), HUSNENI
Radio Frequency Ablation (RFA) is a minimally invasive percutaneous technique with close-loop electric circuit model. Giving the relatively high electrical resistance of tissue in comparison with the electrodes, there is marked agitation of the ions from alternating current with radio frequency 460-550 kHz, present in the tissue that immediately surrounds the electrode. This ionic agitation creates friction within the body and thus heat could be generated. Due to this phenomenon, a temperature within tumor cells could be elevated in range of 50-100 degrees C. In range this temperature, tumor cells become necrosis. Two important steps must be done before RF ablation was applied, i.e volume and location tumor detection , and therapy planning. Therapy planning is very important to make sure that all of tumor tissues are ablated, and prevent ablation of normally tissue around the tumor tissue because of incorrect power and therapy duration, or not all tumor volume are ablated so that ablation technique was applied repeatedly. For these reasons, modeling is applied to observe temperature profile in the tumor tissues with variationof voltage, kind of probe, and duration of ablation. All of variables and parameters in RFA mechanism are characterized and modeled in Bio Heat equation using Finite Element Method (FEM). The results showed that large (width and length) of ablating tissue for needle probe variations with influence of perfusion factor on the same voltage is tend to decrease about 2%-8% on each increase of 1cm-length conduction part of needle probe, otherwise height of ablating tissue is tend to increase about 100%-107% each increase of 1cm-length conduction part of needle probe. Ratio for large of ablating tissue in the same voltage and duration for needle probe based on perfusion factor influence or not are about 1:2. In other hand, different result of temperature measurement and volume tumor ablation between mesh coarser (0.214 cm2/element) and mesh fine (0.024 cm2/element) are about 7%-14%.